Diseño de un sistema de costos por órdenes de producción en la empresa “Puntada Perfecta” en la provincia de Cotopaxi, cantón Latacunga, para el segundo trimestre del año 2022. - Mata Guanotasig, Estefany Araceli (2022)
Faced problem by textile distribution companies is accounting management and costing information, lack knowledge of involved elements in the process to obtain real cost and profitability of finished product, this integrative project is the development of a costing system to suit the needs of Puntada Perfecta company, the main problem is that calculations are made empirically, causing that they do not manage permanece market and not obtain a stable profitability and avoiding to generate waste materials, technology and necessary efforts that can be charged to production cost, through an investigation in backpacks elaboration process, the methodology for data collection has a quantitative approach, for required inquiry a field diagnosis is requested using investigative techniques, interviews, observation sheet and documentary research, these tools allowed, data compilation for development integrative project, identifying raw material, labor and indirect manufacturing costs backpacks manufacture, through information a cost system is designed by production orders in Puntada Perfecta company, to obtain real cost, Excel software was installed and socialized to the owner and manager, in order to set selling price, inventory valuation, better decisions quality products and needs of customers.